Defining the Socially Responsible Leader: Revisiting Issues in Responsible Leadership. (February 2020) - Waldman, David A.; Siegel, Donald S.; Stahl, Günter K.
We renew an exchange of letters from 2008 regarding the meaning of responsible leadership, which applies to senior executives of firms as they attempt to engage in corporate social responsibility. An interesting aspect to this discussion is that, depending on one's theoretical perspective, responsible leadership can be defined in multiple, somewhat disparate ways. We use the terms strategist versus integrator to characterize the most common delineation of responsible leader orientations. While the strategist orientation implies the planning and use of corporate social responsibility initiatives for the direct targeting of return on investment, the integrator orientation involves senior leaders' use of corporate social responsibility to serve the interests of a range of corporate stakeholders. Although a divergence of opinion is expressed in our letters, we concur in our conclusion that more research is necessary to better understand these diverse orientations and their effects on organizations.